Impact of albendazole treatment on the symptom profile of neurocysticercosis patients 14–16 years following diagnosis - Vilela, Lucila; Shahn, Zachary; Carpio, Arturo; Yepez, W. Luis; Di Capua, Daniela; Jaramillo, Alex; Hauser, W. Allen; Quinde-Herrera, Karina; Kelvin, Elizabeth A. (Parasitology, 2025)
Neurocysticercosis (NCC) is a neglected parasitic disease that causes neurological symptoms. However, little is known about the long-term impact of this infection on health. We contacted participants from a randomized controlled trial on albendazole treatment for NCC in Ecuador 12 years after trial completion (14–16 years after NCC diagnosis) about their long-term health. We described the symptoms experienced post-trial and investigated if albendazole treatment, the presence of calcified NC cysts, and cysts in extraparenchymal locations at last imaging predicted symptoms. All analyses were standardized by adjusting for participant age and sex. In the 12 years post-trial, 52.1% reported some health problem, with 48.9% reporting neurological symptoms such as seizures (16.6% of participants) and headaches (26.6% of participants). At the end of the trial, 11 participants had complete NCC cyst resolution, of whom 3 (27.3%) reported seizures and 1 (9.1%) reported headaches post-trial. Twenty-four participants had only calcified cysts (residual calcification sometimes left after the parasite dies) by trial end, of whom 8 (33.3%) reported seizures and 9 (37.5%) headaches post-trial. None of the predictors examined were significantly associated with long-term symptoms. A high proportion of people diagnosed with NCC continue experiencing symptoms years after treatment, and while slightly fewer people experienced continued symptoms in the albendazole group, the difference was not statistically significant. Eleven participants with no live parasites at last imaging (8 with residual calcifications) had seizures post-trial, which may be unprovoked and an indication of epilepsy risk. Research is urgently needed to improve NCC treatment to mitigate long-term outcomes.